2021
DOI: 10.1177/0391398821989334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tocilizumab versus hemoadsorption combined with tocilizumab in patients with SARS-CoV-2 pneumonia: Preliminary results

Abstract: Objective: To assess the variations of Interleukin-6 (IL-6) in patients with SARS-CoV-2 infection treated with Tocilizumab (TCZ) alone or in association with hemoadsorption (HA). Design: Retrospective. Setting: An Intensive Care Unit (ICU) admitting mechanically ventilated patients with SARS-CoV-2 pneumonia. Patients: Four adult patients. Interventions: We compared the blood values of IL-6, C-reactive protein (CRP) and of other biochemical variables including the PaO2/FiO2 in two patients who received TCZ alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…18 Preliminary data in patients with severe COVID-19 pneumonia requiring extracorporeal membrane oxygenation point toward a more pronounced reduction of IL-6 in CytoSorb-treated patients, although the initial level was much higher when compared to a control group. 19 In accord with previous reports, 2022 we also found that IL-6 levels were effectively reduced during hemoadsorption therapy. As systemic hyperinflammation or CRS represents a complex interplay of various mediators, with a high degree of redundancy and overlap in cytokine signaling, the ability of CytoSorb to regulate a wide panel of inflammatory mediators as well as IL-6 might increase its clinical effectiveness.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…18 Preliminary data in patients with severe COVID-19 pneumonia requiring extracorporeal membrane oxygenation point toward a more pronounced reduction of IL-6 in CytoSorb-treated patients, although the initial level was much higher when compared to a control group. 19 In accord with previous reports, 2022 we also found that IL-6 levels were effectively reduced during hemoadsorption therapy. As systemic hyperinflammation or CRS represents a complex interplay of various mediators, with a high degree of redundancy and overlap in cytokine signaling, the ability of CytoSorb to regulate a wide panel of inflammatory mediators as well as IL-6 might increase its clinical effectiveness.…”
Section: Discussionsupporting
confidence: 91%
“…As systemic hyperinflammation or CRS represents a complex interplay of various mediators, with a high degree of redundancy and overlap in cytokine signaling, the ability of CytoSorb to regulate a wide panel of inflammatory mediators as well as IL-6 might increase its clinical effectiveness. 22…”
Section: Discussionmentioning
confidence: 99%
“…All five CytoSorb patients except one survived, and only two of them had to be intubated and mechanically ventilated, while all control patients required intubation and ventilation, and unfortunately died. A small retrospective analysis in four patients with SARS-CoV-2 pneumonia recently reported outcomes in two patients treated with tocilizumab (TCZ) alone and two patients treated with TCZ plus CytoSorb hemoadsorption (HA) [51]. All patients were mechanically ventilated with levels of IL-6, C-reactive protein (CRP), and PaO 2 /FiO 2 ratio measured before, during, and after treatment.…”
Section: Clinical Datamentioning
confidence: 99%
“…In this complex pathophysiological setting involving multiple mediators and high grade of redundancy, overlap, and/or feedback mechanisms, the broad range of action of CytoSorb therapy that targets removal of a variety of inflammatory substances in addition to cytokines could be-at least theoretically-beneficial [51].…”
mentioning
confidence: 99%
“…Dies könnte einige der positiven Auswirkungen dieser Behandlung mit erklären [27]. Im Zusammenhang mit einem kombinierten Einsatz von Tocilizumab und CytoSorb schlussfolgert eine aktuelle Arbeit, dass das Netzwerk von Entzündungsmediatoren, das am Zytokinfreisetzungssyndrom (CRS) bei SARS-CoV-2-Patienten beteiligt ist, so kompliziert und mit so vielen positiven und negativen Rückkopplungsschleifen verbunden ist, dass die Blockade von nur einem Entzündungsmediator − wie etwa mit Tocilizumab − nicht wirksam sein könnte und daher der Einsatz von CytoSorb ratsam erscheint, da es die Entfernung vieler weiterer Entzündungsmediatoren ermöglicht [28].…”
Section: Introductionunclassified